Thyroxine increases Serca2 and Ryr2 gene expression in heart failure rats with euthyroid sick syndrome - Campanha, Fábio V.G. [UNESP]; Perone, Denise [UNESP]; de Campos, Dijon H.S. [UNESP]; de Luvizotto, Renata A. M.; de Síbio, Maria T. [UNESP]; de Oliveira, Miriane [UNESP]; Olimpio, Regiane M. C. [UNESP]; Moretto, Fernanda C. F. [UNESP]; Padovani, Carlos R. [UNESP]; Mazeto, Gláucia M.F.S. [UNESP]; Cicogna, Antonio C. [UNESP]; Nogueira, Célia R. [UNESP] (Archives of Endocrinology and Metabolism, 2016)
Objective: The current study was aimed at analyzing sarcoplasmic reticulum Ca2+ ATPase (Serca2) and ryanodine receptor type 2 (Ryr2) gene expression in rats subjected to surgery that induced HF and were subsequently treated with T4 using physiological doses. Materials and methods: HF was induced in 18 male Wistar rats by clipping the ascending thoracic aorta to generate aortic stenosis (HFS group), while the control group (9-sham) underwent thoracotomy. After 21 weeks, the HFS group was subdivided into two subgroups. One group (9 Wistar rats) with HF received 1.0 µg of T4/100 g of body weight for five consecutive days (HFS/T4); the other group (9 Wistar rats) received isotonic saline solution (HFS/S). The animals were sacrificed after this treatment and examined for signs of HF. Samples from the left ventricles of these animals were analyzed by RT-qPCR for the expression of Serca2 and Ryr2 genes. Results: Rats with HF developed euthyroid sick syndrome (ESS) and treatment with T4 restored the T3 values to the Sham level and increased Serca2 and Ryr2 gene expression, thereby demonstrating a possible benefit of T4 treatment for heart function in ESS associated with HF. Conclusion: The T4 treatment can potentially normalize the levels of T3 as well elevated Serca2 and Ryr2 gene expression in the myocardium in heart failure rats with euthyroid sick syndrome.
Keywords: Calcium channels; Heart failure; Reverse triiodothyronine; Therapeutic use; Triiodothyronine